A systematic review of executive coaching outcomes: Is it the journey or the destination that matters the most? - Athanasopoulou, Andromachi; Dopson, Sue (The Leadership quarterly, 2018)
In this article, we focus on a specific type of personal and professional development practice -executive coaching- and present the most extensive systematic review of executive coaching outcome studies published in peer-reviewed scholarly journals to date. We focus only on coaching provided by external coaches to organizational members. Our purpose is twofold: First, to present and evaluate how executive coaching outcome studies are designed and researched (particularly regarding methodological rigor and context-sensitivity). Secondly, to provide a comprehensive review of what we know about executive coaching outcomes, what are the contextual drivers that affect coaching interventions and what the current gaps in our understanding of coaching practice. On that basis, we discuss and provide a research agenda that might significantly shift the field. We argue that methodological rigor is as important as context-sensitivity in the design of executive coaching outcome studies. We conclude with a discussion of implications for practice.